P-graph for optimising industrial symbiotic networks - Aviso, Kathleen B. (Animo Repository, 2015)
Industrial symbiosis (IS) intends to reduce the consumption of resources as well as reduce the generation of waste streams through utilising by-products of other firms as raw materials of another firm. Mathematical optimisation models have been developed for identifying the optimal design of by-product exchange and utilisation to maximise the benefits of IS networks. However, these models are unable to provide alternative network structures which may have other desirable qualities such as a simpler design, but may be sub-optimal in their realisation of the objective function. Process graph (P-graph) theory is an alternative approach based on graph theory for optimising networks. It has been primarily used for the design and optimisation of process networks, but may be applied to structurally analogous systems. This work thus proposes the development of a P-graph approach for the optimization of IS networks. The methodology is demonstrated using a case study involving a combination of retrofit and grassroots design scenarios, representing existing as well as new plants within an eco-industrial park. The P-graph model is able to provide a graphical representation of the optimal IS system, as well as alternative near-optimal network designs. Copyright © 2015, AIDIC Servizi S.r.l.,.